Perceived Stress, Severity of Xerostomia, and Periodontal Status in Undergraduate Dental Students - Muzhaffar, Engku Ahmad; Berahim, Zurairah; Abdul Wahab, Norsila; Saddki, Norkhafizah (Journal of Dentistry Indonesia, 2023)
Dentistry is a highly stressful program; stress is associated with xerostomia and periodontal disease. Objective: This study aims to investigate the association of perceived stress, severity of xerostomia, and periodontal status in dental students. Methods: This was a two-phase cross-sectional study of 245 Universiti Sains Malaysia (USM) undergraduate dental students. Phase 1 involved administration of the Perceived Stress Scale (PSS-10) and Summated Xerostomia Inventory (SXI). In phase 2, the Community Periodontal Index (CPI) was performed on 150 students to determine their periodontal status. Results: Mean PSS-10 and SXI scores were 19.6 (SD 5.47) and 7.9 (SD 2.04), respectively. Only 7.3% students had healthy periodontium while 17.3% had gingival bleeding, 65.3% had calculus, 6.7% had shallow pockets, and 3.3% had deep pockets. The association of perceived stress, severity of xerostomia, and periodontal status was not significant. Nevertheless, a significant positive correlation was found between PSS-10 and SXI scores (r = 0.318, p < 0.01). Conclusion: Most USM dental students were affected by some degree of periodontal disease, but it was not associated with perceived stress or severity of xerostomia. Students with higher perceived stress had more severe xerostomia. Information from this study could be utilised by the dental school in planning towards providing a stress-free training environment.